Conductive polymers for smart textile applications. (September 2018) - Grancarić, Ana M; Jerković, Ivona; Koncar, Vladan; Cochrane, Cedric; Kelly, Fern M; Soulat, Damien; Legrand, Xavier
Smart textiles are fabrics able to sense external conditions or stimuli, to respond and adapt behaviour to them in an intelligent way and present a challenge in several fields today such as health, sport, automotive and aerospace. Electrically conductive textiles include conductive fibres, yarns, fabrics, and final products made from them. Often they are prerequisite to functioning smart textiles, and their quality determines durability, launderability, reusability and fibrous performances of smart textiles. Important part in smart textiles development has conductive polymers which are defined as organic polymers able to conduct electricity. They combine some of the mechanical features of plastics with the electrical properties typical for metals. The most attractive in a group of these polymers are polyaniline (PANI), polypyrrole (PPy) and poly(3, 4-ethylenedioxythiophene) (PEDOT) as one of the polythiophene (PTh) derivatives. Commercially available smart textile products where conductive polymers have crucial role for their development are medical textiles, protective clothing, touch screen displays, flexible fabric keyboards, and sensors for various areas. This paper is focused on conductive polymers description, mechanism of their conductivity, and various approaches to produce electrically conductive textiles for smart textiles needs. Commercial products of conductive polymers-based smart textiles are presented as well as the objective of a number of lab-scale items.